A multivariate statistical analysis approach for the assessment of water quality in govind ballabh pant sagar reservoir - Varshney R.; Jamal A. (My University, 2025)
Reservoir water is one of the essential sources of water which plays a significant part in not only contributing a sufficient supply of water for industrial operations but it also acts as a source of drinking water. Therefore, contamination of it through industrial, irrigational or any other human intervention can pose a serious threat to it both qualitatively and quantitatively. In the present study, 14 physicochemical parameters of eight sampling sites served as the attribute database represented in form of the correlation matrix for each parameter taking participation in the study. Apart from this, the Water Quality Index of the sampling sites has been enumerated by combining these physicochemical parameters. Hierarchical Cluster Analysis was also performed for grouping the areas having similar grading of water quality index. The overall results indicate that most of the sampling sites were not suitable for drinking purpose and requires treatment of water before use. © RASĀYAN. All rights reserved.